The perception of mobile appliances users on the changes brought to their lifestyle - Alexandru Zalana; Kantor Janos; Silvia Pop; Mariana Pacurar (Amaltea Medical Publishing House, 2020)
Dento-maxilares anomalies can cause severe three-dimensional disorders of the dental arches and implicitly of dental occlusion, interfering with the harmonious development of the physiological dentition, so is necessary to treat the anomalies as soon is possible. The earlier the age of intervention, the higher the success of an orthodontic treatment, having the possibility of guiding the remaining growth, of controlling the dental eruption and permutation, of correcting bad habits by remouvable or fixed appliances. Aim. The authors have done an evaluation of the oral hygiene practices of patients undergoing mobile orthodontic therapy and the impact on their diet and lifestyle in general. Material and method. A questionnaire with 14 questions has been distributed to a number of 63 patients undergoing the active stage of the orthodontic treatment with mobile appliances at the school medical centre in Bucharest, School no. 5. Children aged up to 10 years old have been helped by their parents to fill out this survey, and older children filled out the survey on their own. Results. Most of the respondents have understood the importance of the dental appliance hygiene and teeth hygiene, and then almost in equal shares they have understood also, the importance of diet and of auxiliary means of hygiene. Majority of children (high percentage of the patients 80% ),have indicated that the orthodontic treatment will benefit them an improved esthetic aspect and healthy teeth. They also noticed the importance of the dental appliance hygiene and teeth hygiene, and then have understood , the importance of diet and of auxiliary means of hygiene (89%). Conclusion. There is an obvious tendency of increased desire for an orthodontic therapy within the analyzed population, most of the patients being aware of the role and need to wear an orthodontic appliance.